化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 19:17:39
化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+
化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=
化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=
化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=
{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}
=-sinA*(-tanA)*cotA/((-cosA)*tanA)
=cosA/cosA
=1
化简tan a(cos a-sin a)+sin a(sin a+tan a)/1+cos a
化简:cot^a(tan^a-sin^a)
化简:sin(-a)*cos(-a-兀)*tan(2兀+a) sin(180度+a)*cos(-a)/tan(-a)
化简Sin(180-a)sin(270-a)tan(90-a)/Sin(90+a)tan(270+a)tan(360-a)
化简(sin^2a-tan^2a)*(sin^2a*tan^2a)
化简:{sin(-a)*tan(兀-a)*cot(2兀+a)}/{cos(兀+a)*tan(兀+a)}=
求证:(tan a*sin a)/(tan a-sin a)=(tan a+sin a)/(tan a*sin a)
化简-sin^2(-a)cos(360+a)tan(-a-180)
化简:cot^2A(tan^2A-sin^2A)
化简cot^2 A(tan^2 A-sin^2 A)
cos²(-a)-sin(-a)/ tan(2π+a)化简
化简-sin(180+a)+sin(-a)-tan(360+a)/tan(a+180)+cos(180-a)+cos(-a)
化简:sin^3(-a)*cos(2兀+a)*tan(-a-兀)
化简:sin(2pai+a)tan(pai-a)tan(2pai-a)/cos(-pai-a)tan(3pai+a)
化简 [sin(-a)-sin(900-a)]/[]tan(a-360)-cos(180+a)-cos(-a-360)]
证明恒等式tan a*sin a/tan a-sin a=1+cos a/sin a
cos2(-a)-tan(360+a)/sin(-a)
cos2(-a)-tan(360+a)/sin(-a)